2008
DOI: 10.1080/01426390801948406
|View full text |Cite
|
Sign up to set email alerts
|

Industrially Harvested Peatlands and After-use Potential: Understanding Local Stakeholder Narratives and Landscape Preferences

Abstract: Recent years have witnessed much debate on the turn towards community within landscape management and planning. This is particularly evident in the European Landscape Convention which asserts the legitimacy of local preferences and citizen involvement in policy processes. This paper explores a bottom-up perspective on people-place relationships in a changing landscape, through assessing the after-use potential of industrially mined peatlands in Ireland and the rehabilitation of degraded landscapes. The mining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 49 publications
0
17
0
1
Order By: Relevance
“…Aronson et al 2010 As humans abandon an area, and cease to impart any energy into it, from a landscape level down to individual species and communities, ecological processes will take over in their absence. However, humans do not necessarily just abandon damaged areas completely, so a new relationship emerges (Collier and Scott 2008 and what opportunities may be missed. Therefore, novel ecosystems may present society with opportunities to measure social-ecological resilience, and their paired transitioning could be illuminating on theoretical as well as practical levels.…”
Section: Opportunitymentioning
confidence: 99%
“…Aronson et al 2010 As humans abandon an area, and cease to impart any energy into it, from a landscape level down to individual species and communities, ecological processes will take over in their absence. However, humans do not necessarily just abandon damaged areas completely, so a new relationship emerges (Collier and Scott 2008 and what opportunities may be missed. Therefore, novel ecosystems may present society with opportunities to measure social-ecological resilience, and their paired transitioning could be illuminating on theoretical as well as practical levels.…”
Section: Opportunitymentioning
confidence: 99%
“…In addition, seventeen actors emerged and were also interviewed (n=42) over the research period, having been identified from national and international conference presentations, media appearances, recent appointments or referrals from a key stakeholder. Other local or residential stakeholders (or space-holders, if following the Schmitter (2000) participant definitions in table 2) were interviewed via random, targeted ethnographic sampling and these are reported elsewhere (Collier and Scott, 2008). The interviews reported here yielded a large body of technical information that will be necessary for the potential creation and management of new landscapes after cessation of harvesting.…”
Section: Research Approachmentioning
confidence: 99%
“…Other supposed cultural ecosystem services, such as 'inspiration', 'sense of place' and 'cultural heritage', are likely to have a high value within intact peatland (and indeed all) landscapes, but these have yet to be quantified. An exception of 'social relations', where it is shown that modern communities living within industrial peatlands have associated high social values to these post-mining, recovering landscapes (Collier and Scott, 2008).…”
Section: Industrial Peatlands and Cultural Ecosystem Servicesmentioning
confidence: 99%